Analisis Tingkat Keterampilan Komunikasi Sosial Anak Autis di Surakarta: Mapping Study - Rizki Husadani; Dian Atnantomi Wiliyanto (Journal on Education, 2024)
Children with autism spectrum disorders have several characteristics, namely deficits in the ability to initiate and maintain social interactions, problems with eye contact, limited range of social communication, limited and inflexible behavioral patterns, unusual and excessive interest in activities. Meanwhile, social skills have an important role because social skills include interpersonal behavior, behavior related to oneself, behavior related to academic success, peer acceptance. This research aims to analyze the level of social skills of autistic children. The research uses a quantitative research design with an analytical survey. The research subjects consisted of 16 autistic children. The data collection technique uses the Social-Communication Assessment Tool (S-CAT) instrument to measure the level of social communication of children with autism in the classroom. The results of data analysis seen from the results of the mean percentage (%) carried out by observing using the S-CAT instrument show that the average level of social communication for autistic children consisting of three categories shows a low level, namely 61.92%..